Service to others is the rent that you pay for your room here on earth - Halil, Haikal; Chi Adam, Khairul Bariah; Harun, Nor Adilah (2018)
AIM: 1. To raise general and oral health awareness in the community. 2. To lend a reaching hand to the community, especially the needies and old folks. 3. To create and encourage volunteerism among youngsters with regards of Islamic perspective.